Improving Students’ Mastery of Simple Past Tense By using Real – Life Context Learning Model at Harapan Mandiri Senior High School Medan - Manihuruk, Leonita Maria Efipanias; Manik, Kresna Ningsih; Azzahra Tiara Venya (JURNAL ABDIMAS MADUMA, 2023)
Community service is a form of contribution carried out by individuals or groups to enhance well-being and provide positive benefits to the community at large. This activity is undertaken with the aim of assisting, empowering, and offering solutions to various problems or needs faced by the community. This program was inspired from the writers’ desire to improve the students’ understanding and mastery on Simple Past Tense at Senior High School of Harapan Mandiri School Medan in the third grade XII IPA IV in which the students consisting of 36 students. This program was conducted during one week on August 2023. This activity implements real-life context learning model in improving the students’ understanding and mastery on simple past tenses. This program runs successfully and as it was expected. The students undergo the progress after the program conducted, for instance, the students are able to write the composition using simple past tense with theme such as last holiday or past experiences, they also are able to use the simple past tense to be, modals and verbs in speaking. The Real-Life Context learning model has had a significant impact on education like conducted in Senior High School of Harapan Mandiri Medan, as it has contributed to increased student engagement, motivation, and preparedness for getting learning success especially English. Key words: Simple Past Tense; Real-Life Context Learning Model